Serum Trimethylamine N-Oxide as a Diagnostic and Prognostic Biomarker in Dogs with Chronic Kidney Disease: A Pilot Study - Seung-Ju Kang; Wan-Gyu Kim; Keon Kim; Chang-Hyeon Choi; Jong-Hwan Park; Seog-Jin Kang; Chang-Min Lee; Yoon Jung Do; Woong-Bin Ro (Animals)
Trimethylamine N-oxide (TMAO) is known to increase in human cardiovascular, metabolic, and renal diseases. In human medicine, TMAO has recently been utilized as a diagnostic and prognostic biomarker for renal dysfunction, and research is ongoing regarding its potential as a therapeutic target. This study aimed to evaluate the diagnostic and prognostic potential of TMAO as a supportive biomarker in dogs with chronic kidney disease (CKD). To assess its diagnostic utility, TMAO concentrations were compared between a CKD group (n = 32) and a healthy control group (n = 32). In addition, patients with CKD were subdivided into stages 2 (n = 12), 3 (n = 11), and 4 (n = 9) and compared individually with the healthy controls. For prognostic evaluation, the CKD group was monitored over six months, and the TMAO levels were compared between survivors (n = 18) and non-survivors (n = 14). The TMAO concentrations showed a highly significant difference between patients with CKD and healthy controls (p < 0.0001). Patients with each different CKD stage exhibited statistically significant differences compared with the healthy controls (p < 0.05). Furthermore, the median TMAO levels tended to increase with advancing CKD stage; however, the differences among stages were not statistically significant. In addition, within the CKD group, TMAO concentrations were significantly higher in non-survivors than in survivors at the six-month follow-up (p = 0.0142). This pilot study highlights the potential of TMAO as a supportive renal biomarker for diagnostic and prognostic evaluation in canine CKD.